Analysing banking sector conditions - how to use macro-prudential indicators - Leena Mörttinen; Paolo Poloni; Patrick Sandars; Jukka Vesala (European Central Bank (ECB), 2005)
This paper presents the methodological and statistical framework for macro-prudential analysis of the financial condition of the EU banking sector that has been adopted by the European System of Central Banks (ESCB). The framework is also a central component of broader financial stability assessments carried out by the ECB in co-operation with national authorities. The framework has three main building blocks, which draw on a large number of macro-prudential indicators. The first block is designed for assessing the financial condition of the banking sector. The second building block provides a framework for analysing potential sources of risk and vulnerability to which banks are exposed and an assessment of the importance of related exposures. The final part of the analysis deals with the resilience of banks vis-à-vis these different sources of risk and vulnerability. Analysing the impact of the identified risks on banks' financial condition is the ultimate objective of the ESCB banking sector stability analysis.
Keywords: C82; E44; E58; G21; 330; Financial stability; Banking sector; Macro-prudential analysis and indicators; Financial sector statistics.; Bankrisiko; Messung; EU-Staaten